Psychological care service for children and adolescents convalescing from COVID-19 in Villa Clara - Addys Pérez Fernández; Isaac Irán Cabrera Ruiz; Miguel Ángel Toledo Méndez; Ariadna Martínez Requeiro (Medisur)
Background: children and adolescents constitute a sensitive population to the psychological impacts of the COVID-19 pandemic. Recognizing it implies the need for evaluation, monitoring and intervention, especially when it comes to infants who have suffered from the disease and require comprehensive pediatric care. Objective: to implement a psychological care service for children and adolescents convalescent from COVID-19. Methods: a participatory action research design was applied from a constructive-interpretive qualitative approach. It is made up of three lines of action: psychological evaluation, psychotherapeutic intervention and social support. Its design and implementation followed stages and was carried out collaboratively. The participants involved established symmetrical relationships and followed a cyclical process of planning-acting-observing-reflecting; basic procedure to attend and improve the practice. Results: the results were obtained regarding the evaluation and the actions of psychological intervention. Regarding the evaluation, clinical-psychological alterations with affectation of the psychic functions and needs for the preservation of health in the personal and family spheres stand out. Regarding the psychological intervention, all the beneficiaries received psychological counseling actions and those diagnosed with a psychiatric condition received psychotherapeutic actions. All families received social support. Conclusions: The psychological symptoms intensity reduction or remission was verified, elaboration of grief in the loss, adaptation of coping or behavior modification, strengthening of the social support networks’ capacity, expansion of family knowledge, and creation of information channels between the family and the school.